TRAINING OF PSYCHOLOGICAL AND PEDAGOGICAL DISCIPLINES AS A MEANS OF ENSURING THE NEED-MOTIVATIONAL SPHERE OF FUTURE PRIMARY SCHOOL TEACHERS - Zagorulko, M.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The article is devoted to the study of teaching psychological and pedagogical disciplines as a means of ensuring the need-motivational sphere of future primary school teachers. It is noted that the formation of the personality of the future primary school teacher requires the creation of fundamentally different approaches to professional training in accordance with the modern requirements. The author analyzes the definition of motivation in psychological and pedagogical sources. Motivation is formed and changed in the course of a student's life and, above all, during their academic activities. In the process of activity, new motives, interests and needs are born, which in turn affect the activity. It is important to study the correlation of motives at different stages of personality development and the degree of individual motivation of each student, which will help the teacher to cultivate intrinsic motivation for learning in all students. Considered the concept of the motivational sphere of personality as a set of stable motives that have a certain hierarchy and express the direction of the personality. Motivational sphere in a broad sense is considered as the basis of the personality, which is attracted by its properties such as orientation, value orientations, attitudes, social expectations, claims, emotions, volitional qualities and other socio-psychological characteristics. It is noted that the motivational sphere of the personality is the center of the personality space, where the axes of properties that characterize it intersect. Therefore, the need-motivational sphere cannot be limited to any of the types of motives that are included in it. Needs, motives, goals, emotions, and interests are constantly changing and entering into new relationships. Therefore, the formation of motivation is a constant complication of the structure of the motivational sphere, the appearance of new, more Mature, sometimes contradictory relationships between them. It is noted that through the individualization of the block of psychological and pedagogical disciplines, which is associated with the implementation of individual works, individual educational and research tasks, writing pedagogical essays, we can purposefully influence the needs and motivational sphere of future primary school teachers.